Measuring degradation risk levels of resources in sustainable geotourism development: A multi-criteria decision making (MCDM) approach under spherical fuzzy environments - Kuttusi Zorlu; Selahattin Polat; Volkan Dede; Ali Yılmaz (International Journal of Geoheritage and Parks, 2025)
Natural and anthropogenic processes may deteriorate the integrity of geotourism resources. Thus, one of the top concerns in developing geoconservation measures is determining how risky geosites are for degradation. Although studies have made significant contributions to the literature, they also introduce a fundamental problem of objectivity. In particular, evaluators continue to discuss the objectivity problem caused by hesitant, uncertain, and ambiguous information while evaluating geosites. This study quantifies the risk of degradation of geosites using multi-criteria decision making (MCDM) techniques integrated into fuzzy environments. For this purpose, we used multi attributive ideal-real comparative analysis (MAIRCA) methods based on spherical fuzzy environments in addition to the level based weight assessment (LBWA) technique. We tested this proposed methodology as a case study on twenty geosites selected from the Kula-Salihli UNESCO Global Geopark (KSUGGp) in Türkiye. According to the analysis, we observed significant differences between traditional geosite evaluation approaches and the proposed approach in weighting the criteria and ranking the risk levels of geosites. We expect the proposed approach to make a methodological contribution that can form the basis for the geosite evaluation literature.